Environmental and criminal geoforensics - Pirrie, Duncan; Ruffell, A.; Dawson, L. A. (Special publication / the Geological Society, London, 2013)
Geological techniques are widely used in two aspects of serious criminal investigations: (1) the search for clandestine burial sites, based on near-surface geophysics or through the detection of decomposition signals and (2) the analysis of trace evidence to identify its source location or test the possible association between the trace evidence and a known location of an offence. Although geoforensics is used in such investigations world-wide there are still considerable gaps in the published literature. In addition, there is increasing concern regarding the illegal release of wastes either into the atmosphere, water courses or on to the land surface, and a growing realization that the techniques used in criminal forensics are equally useful in the investigation of environmental crime. This book bridges the gap between environmental and criminal geoforensics with conceptual, methodological and case study contributions. This demonstrates the significant potential that geoforensics holds for investigating and regulatory officers